PELATIHAN DAN PENDAMPINGAN PEMANFAATAN LILIN LEBAH DAN STRATEGI PEMASARAN USAHA MADU KELOMPOK AI SANGER, DESA MATAIYANG - sumarlin, sumarlin; Dewi Seprianingsih; Lidiawati; Ismiati; Sahratullah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Forest honey production in Mataiyang Village, West Sumbawa Regency, plays a crucial role as a primary source of community livelihood but faces challenges related to fluctuating harvests, limited product diversification, and conventional marketing strategies. This Community Partnership Empowerment Program (PKM) aimed to enhance the capacity of the Ai Sanger Farmers Group through training and mentoring in utilizing beeswax as a value-added derivative product and strengthening digital-based marketing strategies. The implementation stages included needs assessment, program socialization, training in processing beeswax into honey soap and aromatherapy candles, and product marketing assistance. The results indicated a significant improvement in participants’ knowledge and skills regarding production techniques and marketing management. Innovative products such as honey soap and aromatherapy candles were successfully produced and marketed through both direct distribution to local retailers and digital platforms, thereby creating opportunities to increase group income. This program demonstrates that the utilization of bee by-products can serve as a sustainable strategy to strengthen the resilience of local honey enterprises and enhance their competitiveness in broader markets.